Transformation of Islamic Cultural History Learning through Wordwall Media: Interactive Solutions to Improve Student Motivation and Learning Outcomes in the Digital Era - Fatkhul Ilma; Sulalah; Samsul Susilawati (Al-Qalam Institute, 2024)
This study focuses on the development and validation of Wordwall as an innovative digital learning media for enhancing student engagement and achievement in Islamic Cultural History, specifically the topic of Khulafaur Rasyidin. Using the Research and Development (R&D) method and the ADDIE model (Analysis, Design, Development, Implementation, Evaluation), this research involved 28 fifth and sixth-grade students at MI Tarbiyyatul Arifin, Malang. Validators included subject matter experts, media specialists, and Islamic Studies educators. Data collection was conducted through interviews, validation sheets, and pretest-posttest assessments. The results indicate that Wordwall achieved an average validation score of 94%, categorized as